Detection and characterization of IgE-binding factors (IgE-BF) within supernatants of the cell line RPMI-8866, normal human sera and sera from atopic patients. - Bujanowski-Weber, J (1988)
IgE-binding factors (IgE-BF) have been shown to be important regulatory factors for IgE induction and suppression. The analysis of IgE-binding factor activity by a modified inhibition radioimmunoassay (RIA), as well as by monoclonal antibodies (mAb) was carried out in the supernatant of the Fc epsilon RII+ cell line RPMI-8866 as well as in human sera. Kinetics of IgE-BF showed optimal release from RPMI-8866 cells after 3-4 days. Gel filtration of the supernatant indicated binding activity at less than 100,000, 45,000 and 25,000 MW. Within normal human sera two peaks of IgE-BF activity were obtained at 45,000 and 25,000 MW. In sera with high IgE levels (atopic dermatitis) a peak at less than 100,000 was MW detected. Within this peak endogenous IgE was present. Addition of sodium dodecylsulphate induced a release of IgE-BF with a MW of 60,000.